Description of two new species of Spininola László, Ronkay & Witt, 2010 (Lepidoptera: Nolidae: Nolinae) from China - Zhang, Huan; Zhang, Wei-Zhong; Guo, Zhen-Yu; Yu, Yong; Huang, Zhen-Fu; Hu, Yan-Qing (Zootaxa, 2024)
The paper describes two new species of Spininola (Spininola zhaotongensis Yu & Hu sp. nov. and Spininola yuanjiangensis Yu & Hu sp. nov.) from Yunnan Province, China. Adults and genitalia are illustrated.